2021
DOI: 10.1002/dvdy.436
|View full text |Cite
|
Sign up to set email alerts
|

Revitalizing mouse diphyodontic dentition formation by inhibiting the sonic hedgehog signaling pathway

Abstract: Background Tooth regeneration depends on the longevity of the dental epithelial lamina. However, the exact mechanism of dental lamina regression has not yet been clarified. To explore the role of the Sonic hedgehog (Shh) signaling pathway in regression process of the rudimentary successional dental lamina (RSDL) in mice, we orally administered a single dose of a Shh signaling pathway inhibitor to pregnant mice between embryonic day 13.0 (E13.0) and E17.0. Results We observed that the Shh signaling pathway inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…Bloomquist et al (2015), on the other hand, found that inhibition in Malawi cichlids of either Wnt, Shh or BMP signalling led to reduced tooth density, but how far these effects were specific for replacement teeth rather than causing loss of functional teeth is not clear from this study. By contrast, inhibition of expression of Shh signalling pathway components in mice revitalises the rudimentary successional dental lamina and leads to supernumerary teeth (Mao et al, 2022). On the other hand, supernumerary teeth have been obtained in zebrafish when upregulating Fgf signalling (Gibert et al, 2010;Jackman et al, 2013), overexpressing ectodysplasin (Eda) signalling (Aigler et al, 2014), downregulating Bmp signalling (Jackman et al, 2013), or administering retinoic acid (Seritrakul et al, 2012).…”
Section: Continuous Tooth Replacement In Teleostsmentioning
confidence: 99%
“…Bloomquist et al (2015), on the other hand, found that inhibition in Malawi cichlids of either Wnt, Shh or BMP signalling led to reduced tooth density, but how far these effects were specific for replacement teeth rather than causing loss of functional teeth is not clear from this study. By contrast, inhibition of expression of Shh signalling pathway components in mice revitalises the rudimentary successional dental lamina and leads to supernumerary teeth (Mao et al, 2022). On the other hand, supernumerary teeth have been obtained in zebrafish when upregulating Fgf signalling (Gibert et al, 2010;Jackman et al, 2013), overexpressing ectodysplasin (Eda) signalling (Aigler et al, 2014), downregulating Bmp signalling (Jackman et al, 2013), or administering retinoic acid (Seritrakul et al, 2012).…”
Section: Continuous Tooth Replacement In Teleostsmentioning
confidence: 99%
“…A recent study indicated that fibulin-1, secreted by fibroblasts in the dental mesenchyme, may regulate the initiation of the successional dental lamina by maintaining a niche of stem cells required for tooth germ formation [113]. SHH signalling may play an inhibitory role in the development of the successional dental lamina: In mice, interference from SHH signalling leads to further development of the rudimentary successional dental lamina of M1 [114]. These results indicate an important role for the successional dental lamina in maintaining a consistent tooth number and potentially influencing tooth number alterations.…”
Section: The Third Direction: Replacement/successional Tooth Developmentmentioning
confidence: 99%